Microsporogenesis and pollen formation in cassava (2011)
This article describes the complete microsporogenesis and pollen formation in cassava (Manihot esculenta Crantz) at the various developmental stages (pollen mother cell, meiosis, tetrads, early free spore, mid uninucleate, late uninucleate, binucleate and mature pollen grain). Light microscopy, transmission electron microscopy and confocal laser scanning microscopy were used for the study. Floral bud size and other inflorescence characteristics were correlated with specific stages of the microspore development. This association allows a rapid selection of floral buds with similar microspore developmental stages, useful when a large number of homogeneous cells are needed for analysis and for in vitro induction of androgenesis. This article also compares methods for digestion the exine wall in microspores.